2022
DOI: 10.3390/metabo12070634
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Metabolic Disorders in Immune Cells and Synoviocytes on the Development of Rheumatoid Arthritis

Abstract: Rheumatoid arthritis (RA) is a progressive autoimmune disease that affects the joints. It has been proven that, with the development of RA, there are changes in the metabolism of cells located in the focus of inflammation. In this article, we describe the connection between metabolism and inflammation in the context of rheumatoid arthritis. We consider in detail the changes in metabolic processes and their subsequent immunomodulatory effects. In particular, we consider how changes in mitochondrial functioning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…The innate and adaptive autoimmunity cells within the interconnected network drive the continuous progression of RA pathogenesis. Numerous studies conducted to date, as well as targeted therapies, have demonstrated that FLSs, macrophages, Th1 cells, and B cells play a pivotal role in initiating and advancing synovial inflammation [85]. Recently, Th17 cells have been implicated as the primary drivers of immune cell activation and cytokine production [60].…”
Section: Discussionmentioning
confidence: 99%
“…The innate and adaptive autoimmunity cells within the interconnected network drive the continuous progression of RA pathogenesis. Numerous studies conducted to date, as well as targeted therapies, have demonstrated that FLSs, macrophages, Th1 cells, and B cells play a pivotal role in initiating and advancing synovial inflammation [85]. Recently, Th17 cells have been implicated as the primary drivers of immune cell activation and cytokine production [60].…”
Section: Discussionmentioning
confidence: 99%
“…1 The basic pathological change in RA patients is chronic inflammation of joint synovium, eventually leading to joint deformity and loss of function. 2,3 Although the etiology and precise molecular processes of RA are still unknown, numerous factors such as environment and genetics, [4][5][6] have been shown to influence the incidence and development of RA. In the pathogenesis of RA, T lymphocytes, and B lymphocytes are particularly critical.…”
Section: Introductionmentioning
confidence: 99%